SMART CONTROL OF WIND-FED BLDC MOTOR DRIVES THROUGH IOT AND SIX-STEP INVERTER TECHNIQUE - K Subha Sharmini; R Vinodha; T Porselvi; K Padmanaban; Minakshi Sanadhya (International Journal of Advances in Signal and Image Sciences)
The Brushless Direct Current (BLDC) motor is extensively used in industrial automation, electric vehicle (EV) propulsion, and renewable energy applications due to its superior efficiency, high speed, rapid response, and operational reliability. However, one notable limitation of BLDC motors is the high transient current during startup, which can lead to rapid battery depletion or reduced lifespan of energy storage systems. To address this challenge, this study proposes an IoT-enabled six-step inverter-based BLDC motor drive system powered by wind energy. The system incorporates a Proportional-Integral (PI) speed controller implemented through a three-phase six-step inverter to regulate the motor's performance. A wireless sensor network collects real-time operational data, which is transmitted to a cloud-based IoT platform for analysis, visualization, and control. The platform features a graphical user interface that facilitates automated monitoring and control of the motor drive. Simulation results confirm that the proposed IoT-based system, combined with the PI controller, effectively tracks and regulates the speed of the BLDC motor under varying load and wind conditions. This integrated approach demonstrates a promising solution for enhancing the efficiency and manageability of wind-powered energy systems using modern motor control and IoT technologies.